Determinants of Demand for Private Health Insurance in Uganda - Turyamureba, Medard; Yawe, Bruno L.; Oryema, John Bosco (African Journal of Economic Review, 2022)
Health insurance coverage in Uganda is still very low, with only five percent of the individuals covered by any form of health insurance. This study examines the factors that influence demand for private health insurance in Uganda using the 2016 Uganda Demographic Health Survey data. A logistic regression model was employed to identify the determinants of demand for voluntary health insurance in Uganda. The results showed that wealth index, level of education, age of the individual, marital status, residence, and access to information were significant factors affecting uptake of health insurance in Uganda. Individuals from well off households were more likely to have a health insurance cover compared to individuals from the poor ones. Also, individuals who had access to information through listening to radio, reading newspapers, and watching television were more likely to demand health insurance compared to those without access. The findings, therefore, highlight the need for poverty reduction strategies to enhance the incomes of the poor and provide educational interventions regarding the benefits of health insurance in all regions.
Keywords: Demand; Health Insurance; Logit